Supplier innovation value from a buyer–supplier structural equivalence view: Evidence from the PACE awards in the automotive industry. Issue 7 (6th November 2019) - Chae, Sangho; Yan, Tingting; Yang, Yang
Abstract: With the growing demand for smarter, cleaner, and safer cars, automotive original equipment manufacturers (OEMs) are increasingly seeking novel inventions from innovative new or foreign suppliers. However, not all innovative suppliers are equally valuable for an OEM. When transforming novel inventions into products, OEMs could find it challenging to work with the suppliers with whom they lack trust or have limited shared understanding. In this study, we adopt a social capital perspective to understand how three types of social capital (i.e., structural, relational, and cognitive) influence a supplier's innovation value to the OEM. Hypotheses are tested using a unique data set combining the supply network structure and automotive supplier innovation award. Our results suggest that it is more difficult to obtain innovation value from a new or culturally distant foreign supplier. However, we also found that suppliers whose networks overlap more with the OEM's network are more likely to provide valuable innovations to the OEM, an effect that is stronger for culturally distant suppliers. This study contributes to the supply network and innovation literature by highlighting the importance of understanding the dyadic social capital between the buyer and supplier when evaluating innovation value of a supplier to a buying firm.